2019
DOI: 10.1590/1678-5150-pvb-6227
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and insulin curve in pregnant mares and its relationship with clinical and biometric features of newborn foals

Abstract: The aim of the present study was to describe the dynamics of glucose and insulin curves in pregnant mares, and to evaluate the curves according to body condition score, identifying the presence of insulin resistance and correlating these values with the weight, height and clinical changes of the neonates. For this, pregnant mares were evaluated and then grouped according to body condition score during the gestation length until lactation. GrM corresponds to mares with moderate body score (BCS 5-6); GrOv were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, glucose levels were higher at parturition in 62 Standardbred mares, 1 and 23 mares (four Percherons and 19 crossbred between Percheron, Belgian, and Breton heavy draft horses), 3 and 26 multiparous pony mares. 18 According to Aoki and Ishii, these alterations could have been due to the physical stress associated with foaling. In the present study, only Quarter Horse mares that delivered healthy, viable full-term foals, without assistance were included.…”
Section: Discussionmentioning
confidence: 99%
“…However, glucose levels were higher at parturition in 62 Standardbred mares, 1 and 23 mares (four Percherons and 19 crossbred between Percheron, Belgian, and Breton heavy draft horses), 3 and 26 multiparous pony mares. 18 According to Aoki and Ishii, these alterations could have been due to the physical stress associated with foaling. In the present study, only Quarter Horse mares that delivered healthy, viable full-term foals, without assistance were included.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that obese mares generally tend to produce larger foals ( 123 ), which coincides with the previously mentioned findings, as both obese and multiparous mares are more likely to have a higher degree of IR ( 5 , 77 ). However, in studies that assessed the direct relationship between mare overnutrition, obesity and foal birth weight, elevated BCS was not found to result in heavier or taller foals ( 14 , 85 , 122 , 139 ), nor did the foal weight or height correlate with the plasma insulin and glucose concentrations of the mare ( 139 ).…”
Section: The Foalmentioning
confidence: 96%
“…-Long-term obesity: Maternal obesity from the time of insemination, together with decreased insulin sensitivity and increased plasma concentrations of inflammation biomarkers in late gestation, did not affect the birth weight, nor the growth of foals when monitored until at least 18 months of age 88,89 .…”
Section: Energy Overfeeding and Obesitymentioning
confidence: 99%